2022
DOI: 10.1111/boc.202200060
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus movement through the hepatocyte: An update

Abstract: Viruses are obligate intracellular pathogens that utilize cellular machinery for many aspects of their propagation and effective egress of virus particles from host cells is one important determinant of virus infectivity. Hijacking host cell processes applies in particular to the hepatitis B virus (HBV), as its DNA genome with about 3 kb in size is one of the smallest viral genomes known. HBV is a leading cause of liver disease and still displays one of the most successful pathogens in human populations worldw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 253 publications
2
8
0
1
Order By: Relevance
“…Finally, HBVwt/C4 mutant presented high levels of extracellular pgRNA, but no difference in extracellular capsid‐associated DNA, suggesting that HBVwt/C4 variants secret more premature pgRNA‐containing particles in which reverse transcription has not been completed. Notably, HBVwt/C4 variant carries mutations in the late assembly domain‐like PPAY motif (P130A and A131P) involved in the transport of mature nucleocapsids to multivesicular bodies via the ESCRT system for viral release 26,27 . It is likely that the mutations in this domain increase extracellular pgRNA levels through the secretion of immature particles via an ESCRT‐independent pathway in detriment of viral progeny production.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, HBVwt/C4 mutant presented high levels of extracellular pgRNA, but no difference in extracellular capsid‐associated DNA, suggesting that HBVwt/C4 variants secret more premature pgRNA‐containing particles in which reverse transcription has not been completed. Notably, HBVwt/C4 variant carries mutations in the late assembly domain‐like PPAY motif (P130A and A131P) involved in the transport of mature nucleocapsids to multivesicular bodies via the ESCRT system for viral release 26,27 . It is likely that the mutations in this domain increase extracellular pgRNA levels through the secretion of immature particles via an ESCRT‐independent pathway in detriment of viral progeny production.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research shows that HBV-related antigens, namely HBcAg and HBsAg, can increase CD4+ T cell production of inhibitory molecules. Chuang et al [ 67 ] found that HBcAg enhanced PD-1 expression on CD4+ T cells, disrupting their function via JNK, ERK, and PI3K/AKT signaling pathways[ 79 ]. Moreover, the expression of human protein inhibitors of activated STAT1 (dependent on ERK and p38 MAPK signaling pathways) increased in CHB patients, making standard therapies ineffectual.…”
Section: Possible Immunological Mechanisms Of Hbv Reactivationmentioning
confidence: 99%
“…The study conducted by Volker Bruss's group demonstrated that the pre-S sequence between Arg 103 and Ser 124 promotes HBV virion assembly ( Bruss, 1997 ). HBcAg forms the icosahedral virus capsid and consists of 183 residues, which can be divided into an assembly domain and a domain responsible for viral genome packaging and replication (arginine-rich RNA-binding C Terminal Domain, CTD) ( Liu et al., 2018 ; Prange, 2022 ; Venkatakrishnan and Zlotnick, 2016 ; Walker et al., 2011 ). Apart from the virologic factors, HBV assembly is also greatly influenced by cellular vesicle trafficking pathways, such as endosomal vesicle trafficking and autophagy, which will be elaborated in the subsequent discussion.…”
Section: Hbv Assembly and Secretionmentioning
confidence: 99%